Safety and effectiveness of hormonal vs non-hormonal or no contraception in women with hypertension and future fertility desire: A broad-scope systematic review - Natalia Losada-Trujillo; Kelly Estrada-Orozco; Oscar Julián Velasco-Lancheros; Brahiam Alejandro Ramírez-Vargas; Álvaro Javier Burgos-Cárdenas; Paula Andrea González-Caicedo; María José Hoyos Bedoya; Hernando Gaitán-Duarte (PLoS ONE, 2026)
Objective To evaluate the safety and effectiveness of hormonal contraceptives compared to non-hormonal methods or no contraception in hypertensive women seeking future fertility. Data sources Searches were conducted in Medline, Embase, CENTRAL, and LILACS (September –October, 2022), with updates on September, 2023, and August, 2024. Clinical trial records, regulatory agencies, and gray literature were also consulted (June, 2022; August, 2023; September, 2024). Methods Eligible studies that assessed safety (major adverse cardiovascular events, pelvic inflammatory disease, vaginal infections, loss of fertility, discontinuation, worsening hypertension, peripheral arterial disease, venous thromboembolism, weight gain, liver or kidney function changes) or effectiveness (pregnancies/Pearl index) of hormonal contraceptives in hypertensive women. Eligible designs included clinical trials, cohort and case control studies, case series, case reports, and adverse event data. Two reviewers independently screened titles/abstracts, reviewed full texts, selected studies, extracted data, and assessed bias (ROBINS-I: cohorts), methodological quality (Newcastle Ottawa: case-control), and critical appraisal (Joanna Briggs Institute: case series). Certainty of evidence was evaluated using GRADE. Evidence was synthesized quantitatively and qualitatively by contraceptive and outcome. Results Of 32,225 records screened, 17 studies were included. Combined oral contraceptives may increase hemorrhagic cerebrovascular disease (OR: 1.64 (95% CI 1.08–2.50, certainty: low). Evidence is very uncertain about their effects on preventing pregnancies, and safety related to ischemic cerebrovascular disease, myocardial infarction, venous thromboembolism, weight gain, hypertension, kidney function, and lipid profile. Similarly, the effects of progestin-only pills, injectables, and vaginal rings on cardiovascular and metabolic outcomes remain highly uncertain. Certainty is also very low for combined oral contraceptives or progestogen-only pills regarding cerebrovascular disease, myocardial infarction (OR: 1.15, 95% CI 0.60–2.19), and peripheral arterial disease. Conclusions Low-certainty evidence suggests that combined oral contraceptives may increase hemorrhagic cerebrovascular disease in hypertensive women, whereas evidence for the other assessed safety and effectiveness outcomes is very low.